Fiber Optic Adaptive Probe as a Cuvette Substitution for UV-Vis Spectrophotometer (Genesis 10S) - Kurniawan, Fredy; Suharmanto, Edi (IPTEK The Journal for Technology and Science, 2014)
Fiber optic adaptive probe UV-Vis for Genesis 10S has been fabricated to substitute cuvette for real time analysis. Most of standard spectrophotometers UV-Vis (the common type) use cuvette to place sample which is being analyzed. The light pass through the sample in the cuvette to detector then the intensity of the absorption of the solution is measured. Most of the cuvette system requires to transferring sample solution to cuvette from its original vessel, so the real time analysis cannot be conducted. The probe with special design using fiber optic cable FT-Au tonics 420-10 has been made to substitute the cuvette system. The light from the source moved inside fiber optic cable, which has been cut in the middle of the cable (the sample can passes through at this gap), to the detector. The end (entrance and exit) of the fiber optic was designed so that it fit to the compartment of the Genesis 10S spectrophotometer without any modification from the standard instrument condition. The spectrum results from the probe in varies gap, in the range 0.2 – 1 cm, was observed. The gap in the middle of the fiber optic was equal to the length of the pathway in the cuvette system. Rhoda mine B was used as the sample with variation concentration 4.175 × 10-5 M, 3.34 × 10-5 M, 2.5 × 10-5 M, and 1.67 × 10-5 M. The spectrum result of adaptive fiber optic probe was compared to the spectrum of standard cuvette system. The optimum result was provided using 0.2 cm gap. The maximum wavelength absorbance of adaptive fiber optic probe was at 533 nm which similar to the cuvette system